Overexpression of Cicer arietinum βIII-Gal but not βIV-Gal in arabidopsis causes a reduction of cell wall β-(1,4)-galactan compensated by an increase in homogalacturonan - Izquierdo, Lucía (Journal of plant physiology, 2018)
Copyright © 2018 Elsevier GmbH. All rights reserved.